Effect of Carrageenan Concentration on The Quality of Coconut Sheet Jam During Storage - Allva Arindya; Rona J. Nainggolan; Linda Masniary Lubis (Universitas Sumatera Utara, 2016)
Coconut production in Indonesia is very abundant, but its processing is still very minimal, therefore the diversification of coconut processing is needed to increase. This study was conducted to determine the effect of carrageenan concentration on the quality of coconut sheet jam during storage. This study used a completely randomized design with two factors namely carrageenan concentration (K): 2,5%, 3,5%, 4,5% and 5,5%, and storage time (L): 0 days, 2 days, 4 days and 6 days. The parameters analyzed were water content, total acid, vitamin C, total dissolved solids, color and texture scores as well as organoleptic values of color, aroma, taste and texture. The results showed that the concentration of carrageenan had highly significant effect on water content, total acid, vitamin C, total dissolved solids, color scores, texture scores as well as organoleptic of color and texture. Storage time had highly significant effect on water content, total acid, total dissolved solids, color scores, texture scores as well as organoleptic of color, taste and texture. Interaction of the two factors had highly significant effect on water content. Concentration of 2,5% carrageenan gave the best quality characteristics of the coconut sheet jam and storage for 6 days was still acceptable for consumption. Keywords: carrageenan concentration, coconut, coconut sheet jam, and storage time.